Studies on the effects of physical parameters of filtration process on the fluid flow characteristics and de-watering efficiency of copper concentrate - Amirhossein Rezaei; Hadi Abdollahi; Mehdi Gharabaghi (International Journal of Mining and Geo-Engineering, 2021)
The effect of physical parameters such as type of filtration media, solids percent, pressure drop, and pH on resistance to filter cloth (R), specific cake resistance (α), moisture content and cake formation rate were investigated in this paper. Experiments were performed using Vacuum Top-Feed method and during the experiments, no chemicals (flocculants, coagulants, etc.) were used. The optimal response for each factor was considered as the minimum values of the resistance to filter cloth (R), specific cake resistance (α), moisture content and maximum cake formation rate. The results showed that the Cloth A7 (Fiber: Polyester, Weave: Twill) and Cloth A12 (Fiber: Polyester, Weave: Plain) have the best performance among 16 types of filters media. With increasing solid content from 45 to 65%, the resistance to filter cloths of A7 and A12 increase from 26.29 (1/m×〖10〗^10) to 101.39 (1/m×〖10〗^10) and from 25.38(1/m×〖10〗^10) to 245.67 (1/m×〖10〗^10), respectively. The highest rate of cake formation in 65% solids for both cloths was 0.077 (mm/s) for cloth A7 and 0.059 (mm/s) for cloth A12. Also, it was found that the compressibility factor is the same for each cloths, so the difference in the compressibility coefficient of cake depends on the inherent properties of the raw material.